TAFSIR QS. AN-NAṢR PERSPEKTIF TAFSIR MAFĀTĪḤ AL-GHAIB DAN RELEVANSINYA DENGAN PROBLEMATIKA KONTEMPORER - Shafa Shafa; Dina Awalia; Wahyu Romadhoni; Cecep Zakarias El Bilad; Akhmad Dasuki (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2026)
This study was motivated by the phenomenon of modern life which tends to reduce the meaning of success into material aspects such as wealth, popularity, and outward achievements. The research problem addressed how QS. An-Naṣr was interpreted in the perspective of Mafātīḥ al-Ghaib by Fakhruddin al-Razi and its relevance to contemporary issues. This study aimed to analyze the concept of success in QS. An-Naṣr and to relate it to modern social phenomena. The method used was qualitative library research with descriptive-analytical and contextual approaches. The findings showed that, according to al-Razi, success was not merely understood as external victory, but as a divine gift that must be responded to through tasbih, praise, and repentance. This perspective also served as a critique of materialistic paradigms that neglect spiritual dimensions. Furthermore, QS. An-Naṣr was found to be relevant to contemporary phenomena such as flexing culture, Fear of Missing Out (FOMO), and the crisis of meaning after success. In conclusion, success in the Qur’anic perspective was not a moment of euphoria, but a point of spiritual reflection that required awareness, humility, and moral responsibility.